Discard survival of coastal elasmobranchs in a small-scale fishery using acoustic telemetry and recapture data. (5th October 2022) - Alonso-Fernández, Alexandre; Mucientes, Gonzalo; Villegas-Ríos, David
Abstract: Discard reduction is a cornerstone of the European Common Fisheries Policy. The discard ban policy, which aims to reduce fisheries discards, is particularly challenging for small-scale fisheries. Demonstrating high survival rates of discarded individuals may provide flexibility to the application of the discard ban through the so-called survival exemption. Here we used acoustic telemetry and mark-recapture data to estimate discard survival of coastal elasmobranch species at multiple temporal scales. We focused on four species targeted by the small-scale fishery in Galicia (NW Spain), one of the most important fishing regions in Europe: Scyliorhinus canicula, Raja undulata, R aja clavata and R aja brachyura . The overall survival rate was 90% on the short term and 85.7% on the long term, but it varied among species. Survival rates of R. clavata and S. canicula on the short term were 70% and 100%, respectively, and 66.7% and 92.9% on the long term, respectively. All the individuals of R. brachyura and R. undulata survived on the long term. Our results are critical to support the application of survival exemption in small scale fisheries. Graphical abstract: Image 1 Highlights: The EU discard ban policy is challenging for the small-scale fishing fleet. The survival exemption provides flexibility to the application of the discard ban. Survival of coastal elasmobranchs in NW Spain was estimated using acoustic telemetry. The survival rate ranged from 66 to 100%.